2014
DOI: 10.1016/j.placenta.2014.06.261
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation and regulation in preeclamptic placenta

Abstract: † Anna Inkeri Lokki and Jenni Heikkinen-Eloranta have contributed equally to this work.Preeclampsia (PE) is a common disorder of pregnancy originating in the placenta. We examined whether excessive activation or poor regulation of the complement system at the maternal-fetal interface could contribute to the development of PE. Location and occurrence of complement components and regulators in placentae were analyzed. Cryostat sections of placentae were processed from 7 early-onset PE (diagnosis <34 weeks of ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 36 publications
0
43
0
1
Order By: Relevance
“…Most studies have examined term placenta available after normal birth or early placenta obtained at abortion. Lokki et al (Lokki et al, 2014) probed for plasma regulators of complement activation in term placenta and demonstrated C4BP evident in syncytial bodies or areas of damaged syncytiotrophoblasts and Factor H in tissue stroma. Buurma (Buurma et al, 2012) clearly documented message for CD46, CD55 and CD59 in placenta during normal pregnancy.…”
Section: Complement System and Normal Pregnancymentioning
confidence: 99%
“…Most studies have examined term placenta available after normal birth or early placenta obtained at abortion. Lokki et al (Lokki et al, 2014) probed for plasma regulators of complement activation in term placenta and demonstrated C4BP evident in syncytial bodies or areas of damaged syncytiotrophoblasts and Factor H in tissue stroma. Buurma (Buurma et al, 2012) clearly documented message for CD46, CD55 and CD59 in placenta during normal pregnancy.…”
Section: Complement System and Normal Pregnancymentioning
confidence: 99%
“…Multiple studies demonstrated significantly enhanced systemic complement system activation in preeclamptic pregnancies compared to normal pregnancies (Derzsy et al, 2010; Regal et al, 2015a). Both the placenta and kidney also showed evidence of increased local complement activation in preeclampsia, coincident with up-regulation of message for complement regulators but no evidence of changes in regulator expression using immunohistochemistry have been reported (Burwick et al, 2014; Buurma et al, 2012; Lokki et al, 2014; Penning et al, 2015). However, the event or events that initiate complement activation in preeclampsia are unknown.…”
Section: Introductionmentioning
confidence: 97%
“…En pacientes trasplantados se ha documentado depósitos de C1q en aloinjerto renal, aunque su prevalencia es baja 0.4%, el papel pronóstico en el paciente transplantado aún no está muy claro [7] En una revisión de Inkeri y cols se menciona que la excesiva activación del complemento y depósitos de C1q en placenta se relacionan con preeclampsia y abortos, a pesar de una evidencia pobre, no descartamos que en la paciente las perdidas recurrentes del embarazo pudieran estar en relación con esta patología [8].…”
Section: Discussionunclassified